Letting go of Managing? Struggles over Managerial Roles in Collaborative Governance - Plotnikof, Mie (Nordic Journal of Working Life Studies, 2016)
This article discusses the role of the manager in collaborative governance studies. These studies identify a new managerial role as facilitator of stakeholder collaboration when pursuing public policy and service innovation. But the complications of role changes are underexplored; hence this article addresses the emerging challenges. Drawing on organizational discourse studies, it theorizes and analyzes managers’ positioning during collaborative governance practices in cases from the Danish daycare area. The findings demonstrate how public managers construct old and new roles related to various public management discourses, and their struggles to change accordingly. However, the findings also show how managers empower their new role and gain agency to steer collaborative outcomes. Thereby the article unpacks the challenges of becoming a facilitating manager alongside other roles: the struggles of identity and agency constitutive to particular ways of managing, as well as struggles over multiple roles. It suggests paying greater attention to constitutive aspects of changing roles to understand the managerial challenges and effects implied through emerging public management discourses.